Receiving sacrament anointing of the Sick - JANCZEWSKI, ZBIGNIEW (Prawo Kanoniczne, 2012)
Receiving of sacraments, including anointing of the sick should be performed according to the rules of Christ and the Church which are listed in canon and liturgical law. These rules were discussed in the above publication. At the beginning a brief historical introductory to this topic made followed by detailed interpretation of canon 1004. Word “danger” is used as a key word describing a receiver of the sacrament listed in the 1983 Code of Canon Law. Another topic mentioned in the publication is a possibility of receiving the sacrament of anointing of the sick by a larger group of people during some kind of liturgical celebration. In this case there is possibility of misuse of this law. The publication also discusses skepticism of the receiving the sacrament by a person with a limited use of reason, terminally ill or when seriousness of the illness is doubt. The last section of the publication is devoted to limitation of receiving the above sacrament.